Methyl-CpG Binding Protein 2 (Mecp2) Regulates Sensory Function Through Sema5b and Robo2 - Leong, Wan Y.; Lim, Zhi H.; Korzh, Vladimir; Pietri, Thomas; Goh, Eyleen L. K. (Frontiers in Cellular Neuroscience, 2015)
Mutations in the gene encoding the MECP2 underlies Rett syndrome, a neurodevelopmental disorder in young females. Although reduced pain sensitivity in Rett syndrome patients and in partial MeCP2 deficient mice had been reported, these previous studies focused predominantly on motor impairments. Therefore, it is still unknown how MeCP2 is involved in these sensory defects. In addition, the human disease manifestations where males with mutations in MECP2 gene normally do not survive and females show typical neurological symptoms only after 18 months of age, is profoundly different in MeCP2-deficient mouse where all animals survived, and males but not females displayed Rett syndrome phenotypes at an early age. Thus, the mecp2-deficient zebrafish serves as an additional animal model to aid in deciphering the role and mechanisms of Mecp2 in neurodevelopment. Here, we used 2 independent methods of silencing expression of Mecp2 in zebrafish to uncover a novel role of Mecp2 in trigeminal ganglion sensory neurons during the embryonic development. mecp2-null mutation and morpholino-mediated silencing of Mecp2 in the zebrafish embryos resulted in defects in peripheral innervation of trigeminal sensory neurons and consequently affecting the sensory function. These defects were demonstrated to be dependent on the expression of Sema5b and Robo2. The expression of both proteins together could better overcome the defects caused by Mecp2 deficiency as compared to the expression of either Sema5b or Robo2 alone. Sema5b and Robo2 were downregulated upon Mecp2 silencing or in mecp2-null embryos, and Chromatin immunoprecipitation (ChIP) assay using antibody against Mecp2 was able to pull down specific regions of both Sema5b and Robo2 promoters, showing interaction between Mecp2 and the promoters of both genes. In addition, cell-specific expression of Mecp2 can overcome the innervation and sensory response defects in Mecp2 morphants indicating that these MeCP2-mediated defects are cell-autonomous. The sensory deficits caused by Mecp2 deficiency mirror the diminished sensory response observed in Rett Syndrome patients. This suggests that zebrafish could be an unconventional but useful model for this disorder manifesting defects that are not easily studied in full using rodent models.